The Validity Ethnobotany Book of Jatropha gossypiifolia In The Coastal Forest Area Of Tabanio - Aulia Rahman; Dharmono Dharmono; Sri Amintarti (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2020)
One of the urgent problems in Ethnobotany learning is the lack of learning resources. Jatropha gossypiifolia is one of the plants found in the Tabanio Coastal Forest Area, Tanah Laut Regency, and has the potential to be used as a learning resource. The potency of the Jatropha gossypiifolia plant as a learning resource, teaching materials are made in the form of a scientific book on the study of ethnobotany Jatropha gossypiifolia plants in the Tabanio coastal forest as supporting material for the Ethnobotany course. This study aims to describe the validity of scientific books has developed by plant ethnobotany Jatropha gossypiifolia. This as supporting material for Ethnobotany courses. This study uses a research development method with the Education Design Research (EDR) model with a formative evaluation of the Tessmer test. This scientific book "Study of Plant Ethnobotany Jatropha gossypiifolia Tabanio Beach Forest" has been stated by two valid validated validators with a validity score of 93.75%, and individual tests with a score of 92.11% were in the excellent category.AbstrakSalah satu permasalahan penting dalam pembelajaran Etnobotani adalah kurangnya sumber belajar. Jatropha gossypiifolia adalah salah satu tumbuhan yang terdapat di Kawasan Hutan Pantai Tabanio Kabupaten Tanah Laut berpotensi dijadikan sebagai sumber belajar. Oleh karena potensi tumbuhan Jatropha gossypiifolia sebagai sumber belajar maka dibuat bahan ajar berupa buku ilmiah tentang kajian etnobotani tumbuhan Jatropha gossypiifolia hutan pantai Tabanio sebagai materi penunjang mata kuliah Etnobotani. Penelitian ini bertujuan untuk mendeskripsikan validitas buku ilmiah yang dikembangkan tentang Etnobotani Tumbuhan Jatropha gossypiifolia sebagai materi penunjang mata kuliah Etnobotani. Penelitian ini menggunakan metode penelitian pengembangan dengan model Education Design Research (EDR) dengan evaluasi formatif uji Tessmer. Buku ilmiah yang dikembangkan berjudul Kajian Etnobotani Tumbuhan Jatropha gossypiifolia  Hutan Pantai Tabanio dinyatakan oleh dua validator bernilai sangat valid dengan skor validitasnya 93,75% dan untuk uji perorangan mendapatkan skor 92,11% dengan kategori sangat baik.